Eminence and Contributions of the Companions in the Development and Teaching of the Qur’ān in the First Hijri Century - Norazman Alias; Nor Hafizi bin Yusof (Journal of Islamic Thought and Civilization, 2024)
The process of Qur’ānic teaching in the Islamic world began during the Era of Revelation. Islamic history proves that the Qur’ān was inherited through talaqqī bi al-Mushāfahah (direct oral transmission) from teacher (murshid) to student, passing through a chain of teachers until it reaches the source of its revelation that is Prophet Muḥammad. The companions of the Prophet played a significant role in spreading the message of Islam across the world during their time by teaching the Qur’ān to the Ummah (Muslim community). A significant number of modern Muslims don't have much knowledge about Islamic history, including the vital roles played by the companions in shaping and disseminating the teachings of the Qur’an. This research aims to provide a brief overview of the early history of the development and teaching of the Qur’ān in the first century of the Hijri and explored the scholarship of the companions involved. The study utilised a literary method and a historiographical approach. Each historical fact recorded was analysed through the process based on inductive (taḥlīli), deductive (istinbāṭ), and comparative (muqāranah) methods, while relying on the historical references as primary sources authored by the Islamic scholars. The findings revealed that a significant number of companions, not only Muslim men but also women, played an essential role in disseminating the Qur’ān during the first century of the Hijri calendar.